Addictive substances problematic approaches in textbooks of 16 countries - Carvalho, Graça Simões de (2008)
Addictive substances, such as alcohol, tobacco and other drugs, represent a serious problem in the actual society. Young people are very vulnerable to these substances consumption, and UNESCO has recognized the school as an important setting for addiction prevention, included in the global plan of the Health Education. School can be a place where young pupils may contact with drugs and fall in such world or, in contrast, where they may become aware of this reality and become empowered to make responsible healthier choices. The aim of this work was to compare addictive substances approaches in textbooks within 16 countries involved in the European project “Biohead-Citizen”. We used a specific part of the project grid for substances abuse (alcohol, tobacco and other drugs) concerning five major indicators: physical effects, psychological effects, social effects, preventive campaigns and environmental (and social) approaches. Countries present different approach levels according to the kind of substance. These issues are explored preferentially in text but in some countries some substances are not referred. The comparative analyses highlighted the Finish textbook as the most comprehensive one, which may be associated to the fact that Finland is the only country having a specific Health Education teaching module.